Pars Plana Vitrectomy Combined with Focal Endolaser Photocoagulation for Idiopathic Macular Telangiectasia - Gaku Terauchi; Celso Soiti Matsumoto; Kei Shinoda; Harue Matsumoto; Yutaka Imamura; Emiko Watanabe; Takaaki Kondo; Atsushi Mizota (Case Reports in Medicine)
Background. To report the outcome of pars plana vitrectomy (PPV) combined with intraoperative endolaser focal photocoagulation (PC) on eyes with idiopathic macular telangiectasis (MacTel) type 1. Methods. This was a retrospective study of two female patients with MacTel type 1 who were resistant to focal photocoagulation, sub-Tenon triamcinolone injection, and/or antiangiogenic drugs. The best-corrected visual acuity (BCVA) was determined, and fluorescein angiography (FA) and spectral domain optical coherence tomography (SD-OCT) were performed before and after surgery for up to 19 months. Results. After surgery, the BCVA gradually improved from 20/100 to 20/20 at 19 months in Case 1 and from 20/50 to 20/13 at 13 months in Case 2. Fluorescein angiography (FA) showed leakage at the late phase, and OCT showed that the cystoid macular edema was resolved and the fovea was considerably thinner postoperatively. Conclusion. Patients with MacTel type 1 who are refractory to the other types of treatments can benefit from PPV combined with intraoperative endolaser focal PC with functional and morphological improvements.